Neighbourhood Relations - Solovjovas, Nikolajus (Problemos, 1975)
In the literature on the town-sociology some authors say that losing touch with neighbourhood is an inevitable phenomenon among town-folk. The authors of the paper express their doubts as to the categoric nature of like assertions and hold that there is still place for neighbourly links in modern urban environment. If the earlier stages of urban civilization neighbourly links were manifest in the consanguine, class or economical form, it is characteristic of the present stage of their development that there are possibilities to choose freely. The social practice of the USSR and other socialist countries proves it. The authors present certain proposals as to the most important town-building and practical measures for stimulating neighbourly contacts of a new type as the most significant aspect of socializing the personality.